Investigation of Cytotoxicity Properties of Novel Phthalocyanine Complexes Containing Chalcones Groups on Different Cancer Cell Lines - Tekin, Suat; Koran, Kenan; Gorgulu, Ahmet Orhan; Sandal, Suleyman (Wiley, 2017)
[Abstract Not Available]